Film-induced tourism: a systematic literature review - Lucília Cardoso; Cristina Estevão; Cristina Fernandes; Helena Alves (Tourism & Management Studies)
The “film-induced tourism” concept serves for the study of tourism visits made to a destination or attraction resulting from its featuring in cinema films, television series or promotional videos. This phenomenon falls within the field of “film-induced versus destination branding image” research, a fairly recently established field, and with this article correspondingly seeking to carry out analysis of the contents and systematisation of this area based on the contents of the Web of Science database. Thus, this article consists of the application of a systematic survey involving the summary and evaluation based upon the interpretation of the results returned. The sample contains only those articles published in English language journals and explicitly excluding conference proceedings or commentaries. We thus sought to grasp the perspectives adopted by both empirical and theoretical studies, the themes studied and the main conclusions of those studies analysed here. The results convey the diversity of both the quantitative and qualitative studies and the various future lines of research defined in accordance with the gaps detected in the results returned.